ANALISIS KESALAHAN SISWA BERDASARKAN PROSEDUR POLYA DALAM MATERI PECAHAN DI KELAS VIII SMP NEGERI 1 LUAHAGUNDRE MANIAMOLO TAHUN PELAJARAN 2022/2023 - Laia, Hesti Lestari (Universitas Nias Raya, 2023)
This research was motivated by many students having difficulty solving story problems on fractional material. The aims of this study were (1) to find out students' errors based on the polya procedure in the fraction material in Class VIII SMP Negeri 1 Luahagudre Maniamolo in the 2022/2023 academic year, (2) to find out the causes of student errors based on the polya procedure in completing the fraction test in Class VIII SMP Negeri 1 Luahagudre Maniamolo Academic Year 2022/2023. This study uses a qualitative research method with a descriptive approach. Data were collected using learning outcomes tests and interviews. The results showed that students who made mistakes in understanding the questions were 6 people, students who made transformation errors were 4 people, students who did process skills were 9 people, while for errors in determining the final answer consisted of students who made all the mistakes above. Conclusions (1) student errors based on the polya procedure in fractional material are misunderstandings about the problem, transformation errors, process skills errors and final answer errors, (2) the factors causing student errors in working on story questions on fractional material are difficulty understanding the problem, lack of understand the concepts and operations of fractions and are less thorough in solving problems. Suggestions, given the importance of story problem material in mathematics, it is better for teachers to be able to apply story problem learning more intensively using more varied models accompanied by teaching aids, so that students can be more motivated to learn story questions.